Upaya Kepemimpinan Spiritual dalam Mengembangkan Budaya Mutu di SMA Plus Muthahhari Bandung - Erba Rozalina Yuliyanti; Didin Saepuddin; Yunasril Ali (JURNAL INDO-ISLAMIKA, 2015)
This paper aims to obtain information about the spiritual leadership efforts in developing a culture quality and its reality developed. The method in this study is a qualitative descriptive method. This research is a single case study focusing on the private Islamic schools, Senior High School Plus under Motahhari foundation, Bandung. The main data were obtained from primary sources namely the headmaster, teachers, staff, students and parents. Then, the secondary sources are qualitative documents such as dissertations, journals, documents and other sources supporting data. The data were collecting indepth interviews, non-participant observation and documentation. The technique of data analysis use integrative analysis. Then the data were analyzed using three methods namely data organization, data reduction and data presentation. For checking the validity of the data, researcheruse: 1) the credibility of the data with triangulation techniques, dependability and confirmability. The findings of study showed: 1) an articulation and dissemination of the vision and mission of the school was implemented fairly intense, 2) Motahhari as a symbol of Ulul Albab development, 3) the rewards and sanctions formes are an extrinsic and an intrinsic, 4) the relationships that occur in school is a social, an emotional and a spiritual relationships. The reality of the quality culture developed are: 1), cultural empathy, 2) critical culture, 3) an innovative culture, and 4) an inclusive - pluralist culture